Characterization, Acid Activation, and Bleaching Performance of Ibeshe Clay, Lagos, Nigeria. (1st March 2012) - Usman, M. A.; Ekwueme, V. I.; Alaje, T. O.; Mohammed, A. O.
Abstract : This paper investigated the possibility of using clay characterization as a major tool to predict its suitability for bleaching of vegetable oil, namely, palm oil. The clay sample collected from Ibeshe deposit was characterized by X-ray diffraction (XRD). The results of the XRD showed that the clay is composed of dioctahedral kaolinite and dickite, silica, ilmenite, and merlinite. The compositional analysis using atomic absorption spectroscopy (AAS) showed that the Na2 O : CaO ratio is 0.22, a value less than one and indicative of the absence of bentonite which presence, just like montmorillonite, confers bleaching activity to clays. Furthermore, the SiO2 : Al2 O3 ratio of 1.12 (greater than one) is suggestive of a clay suitable not for bleaching but for zeolite development. Actual laboratory tests for bleaching performance evaluation confirmed the prediction above that the clay indeed has poor bleaching action as shown by percent colour reduction. The colour reduction for natural clay was 9.1%. This value only increased to 27.3% after 3M HCl activation, a value still very low for effective bleaching.